Patti Lateranensi. Un accordo tra lo Stato Fascista e la Santa Sede - Sternalski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The publication refers to the creation of the Vatican City State. It presents the history of “The Roman Question” la questione romana which began on September 20, 1870 when the army of the King of Italy, Victor Emmanuel II conquered Rome, capital of the Papal States. It then describes the evolution of Italian politics and the relations of Benito Mussolini and Italian fascism to Pope Pius XI, the Holy See and the Catholic Church. The author reconstructed the secret negotiations led by Francesco Pacelli Holy See and Domenico Barone Italy which ended in signing agreements. At the end it describes the provision of the Lateran Treaties and the course of their ratification.
Keywords: Włochy; Watykan; Stolica Apostolska; faszyzm; traktaty laterańskie